Implementasi Pendidikan Inklusif dalam Pemenuhan Hak Anak Berkebutuhan Khusus di Kalimantan Selatan - Insan Firdaus (Jurnal HAM, 2015)
Inclusive education is one of the government's efforts to fulfill the right to education for Children with Special Needs. The essence of Inclusive Education is to provide space and opportunities for children with special needs to get education as children in general without discrimination. Era of regional autonomy, the implementation of inclusive education is the responsibility of local governments. Therefore, the local government has an important role in the success of inclusive education. Kalimantan Selatan is a province that is a pioneer in the delivery of inclusive education. This study discusses how the implementation of inclusive education in Kalimantan Selatan. This study used a qualitative approach supported by quantitative data on four indicators of the fulfillment of the right to education, namely availability, affordability, acceptability and adaptable. It can be concluded that the government of Kalimantan Selatan province strongly supports the implementation of inclusive education, but in practice there are still obstacles, among others, the availability of inclusive schools that have not been evenly distributed in each district, the availability of guidance counselor particular, means of infrastructures supporting inclusive education and understanding and awareness of local leaders and community towards inclusive education.